2021
DOI: 10.21203/rs.3.rs-690031/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wastewater-based epidemiology predicts COVID-19 community prevalence

Abstract: Wastewater-based epidemiology uses pooled wastewater samples to monitor community health and has been used extensively during the COVID-19 pandemic to track SARS-CoV-2 RNA shed by infected individuals into wastewater. Wastewater concentrations of SARS-CoV-2 RNA have been positively correlated with contemporaneous counts of COVID-19 cases, making it useful for following relative disease burden trends within a community. However, the statistical associations are too weak for wastewater-based epidemiology to rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Several WBE studies have reported known numbers of infected individuals. A number of these studies were performed on college campuses and correlated SARS-CoV-2 RNA concentrations to reported cases. Of these, Karthikeyan et al provided a model to quantitatively link RNA concentrations to numbers of cases. They employed an infinite impulse response filter with wastewater signal as an input.…”
Section: Introductionmentioning
confidence: 99%
“…Several WBE studies have reported known numbers of infected individuals. A number of these studies were performed on college campuses and correlated SARS-CoV-2 RNA concentrations to reported cases. Of these, Karthikeyan et al provided a model to quantitatively link RNA concentrations to numbers of cases. They employed an infinite impulse response filter with wastewater signal as an input.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our results do not support a linear relationship between wastewater and prevalence proposed by Layton et al . 10 and Cao et al . 13 Previous convenience seroprevalence studies paired to wastewater may have underreported the correlation, owing to inadequate or no case data from portions of a community, underreporting of at-home COVID-19 antigen rapid self-test results, and reliance on clinical syndromic surveillance.…”
Section: Discussionmentioning
confidence: 95%
“…Previous combined wastewater and serological surveys at a community scale have focused on Hepatitis A and E viruses. 11,12 Existing SARS-CoV-2 wastewater to community COVID-19 case models have been fit around results obtained from convenience sampling, models which may underrepresent community trends, 1317 as well as limited random samples of communities via SARS-CoV-2 in nasal swabs 10 or blood bank serological surveys. 15,18 Nonetheless, robust longitudinal estimates of community serology are more appropriate to interpret wastewater measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution of assigned flags (“minimal review required”, “review suggested”, “review strongly suggested”, “not available in the main text”, “not applicable”) for the top 11 categories in the structured ethical review, represented as a fraction percent of all publications analyzed ( n = 53) with multiple reviewers providing reports for select individual studies, resulting in more reviews than studies ( n = 79). , , In total, 56 publications were represented by these studies, with 3 having two publications describing the same monitoring campaign and considered in concert. The categories are sorted by ascending proportion of “minimal review required”.…”
Section: Resultsmentioning
confidence: 99%